Quezon and his business friends notes on the origins of Philippine national capitalism - Caoili, Manuel A. (1987)
Much of Quezon's political and economic policies centered on creating a home-grown industrial base which in its infancy was pitted against the more influential American industrial complex. Despite charges of patronage and undue use of political influence, Quezon relied heavily on his business associates to support his administration's economic policies and projects. Quezon's failure to effect long lasting structural changes was brought about by his fear of antagonizing the Americans with protectionist policies in order to speed friends, most of whom belonged to the landed elites and the prominent families in Philippine society.
Keywords: Quezon, Manuel L., 1878-1944; Philippines -- Economic policy -- 1935-1946; Philippines -- Literary collections -- 1935-1946